2002
DOI: 10.1509/jmkr.39.2.242.19081
|View full text |Cite
|
Sign up to set email alerts
|

Pleasant Surprises: Consumer Response to Unexpected In-Store Coupons

Abstract: This article studies the impact of in-store "surprise" coupons (e.g., electronic shelf coupons, peel-off coupons) on consumers' total basket of purchases. A conceptual model is developed that (1) predicts that the use of a surprise coupon will increase the size of the shopping basket and the number of unplanned purchases made on the shopping trip and (2) predicts the type of these unplanned purchases. The authors present the results of an in-store experiment and analysis of the Stanford Market Basket Data to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
172
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(198 citation statements)
references
References 15 publications
16
172
1
Order By: Relevance
“…Thus, we expect that compared with cash, credit card use will increase the likelihood of unplanned purchases. 3 The coupon was mailed to respondents to prevent a windfall effect (e.g., Heilman, Nakamoto, and Rao 2002).…”
Section: Methods Of Paymentmentioning
confidence: 99%
“…Thus, we expect that compared with cash, credit card use will increase the likelihood of unplanned purchases. 3 The coupon was mailed to respondents to prevent a windfall effect (e.g., Heilman, Nakamoto, and Rao 2002).…”
Section: Methods Of Paymentmentioning
confidence: 99%
“…Arkes et al (1994) demonstrated that unexpected small windfalls ($3-5) are more likely to be spent on gambling or at a basketball game than anticipated windfalls of the same size. Heilman et al (2002) examined the effect of $1 coupons for particular grocery items on the behavior of grocery shoppers and found that the coupons increased consumers' unplanned spending as well as their total spending. 6 Finally, in research contemporaneous with ours, Abeler and Marklein (2008) studied how restaurant patrons responded to an unexpected windfall in the form of a discount on their bill.…”
Section: Related Empirical Literaturementioning
confidence: 99%
“…Thus, marketers commonly use a long-wavelength color (e.g., red) in the prepurchase stage (e.g., advertisement) to stimulate arousal (Mehta and Zhu 2009) (e.g., excitement) and tend to use a short-wavelength color (e.g., blue) in the postpurchase stage to lower arousal (e.g., relaxation). Gifts or coupons, as an effective promotion strategy, can create a positive surprise when they appear in the package (Heilman et al 2002). This positive surprise may cause consumers to experience greater perceived pleasure and perhaps even arousal.…”
Section: Affective Reactions In Consumer Return Behaviormentioning
confidence: 99%